Speckle Tracking Derived Left and Right Atrial, Left and Right Ventricular Strain, Strain Rate After Atrioventricular Node Slow Pathway Radiofrequency Ablation - Sileikiene, R.; Vaskelyte, J.; Mizariene, V.; Jurkevicius, R.; Bluzaite, I. (Elektronika ir Elektrotechnika, 2011)
Impairment of atria and ventricular function may occur after radiofreąuency ablation (RFA) of AV node slow pathway in the case of tachycardia. The 2D speckle tracking imaging technique was used for quantification of global and regional function of the heart at late follow-up in children who underwent RFA of slow pathway. The study group consisted of 22 children who underwent RFA 5, 5 (2,5) years ago and 20 healthy children. The age was comparable between the groups. The study revealed no impairment of global and regional function of the ventricles and increased atria volumes, reduced regional atrial myocardial deformation parameters in children late after RFA. One of the possible cause of reduced atrial function may be negative effect of radiofrequency ablation. Bibl. 11, tabl. 9 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.109.3.171